Hasil Belajar Ipa Kelas IV SD di Gugus II Santalia Melalui Tutor Sebaya - Sarini, Ni Komang; Sudana, Dewa Nyoman; Riastini, Putu Nanci (Jurnal Ilmiah Sekolah Dasar, 2018)
This study is aimed find out significant difference of natural science learning outcomes of students who follow peer tutor and do not follow peer tutor. This study is quasi experimental study especially non-equivalent post tes only kontrol groip design. The population of this study was the entire of IV grade students in Gugus II Santalia Kubutambahan District. The sample was determined by using random sampling technique. The sample was IV grade students if SDN 2 Kubutambahan was chosen as experimental group and class IV SDN 4 Kubutambahan as control group. The data was teken by using multiple choice test. The data obtained were analized by using descriptive statistical analysis and inrerential statistic t-test with the formula of polled variance. The results showed the lessons with peer tutor and the group of students who do not follow peer tutor. the findings are peer tutor makes the students motivated, trained, and active to espress their option. furthermore, peer tutor provides an opportunity for the students to exchange ideas, and their work together. in addition, learning with peer titor becomes fluent communicating